Political Science: Realism In Roberts's Animal Stories - Dean, Misao (Studies in Canadian Literature, 1996)
Charles G.D. Roberts's animal stories are regularly discussed as an attempt to create a new kind of animal character, one that is not an anthropomorphic copy of human psychology nor a one-dimensional allegory, but instead a "real" animal based on accurate observation and up-to-date science. However, since no realism is transparent, Roberts's stories cannot be expected to neutrally reproduce reality, despite their modernist techniques. Indeed, what Roberts's "animal biographies" choose to signify as "real" -- human, masculine selfhood concerned with hierarchical power structure, as well as a unified autonomous human personality as universal phenomenon -- is as important as the ways in which these notions are signified. The stories function as ideology and do the work of politics; they occupy a place in the critical narrative of the development of realism in Canadian fiction by constructing the reader as subject, "naturally predatory," material, and male.